2014
DOI: 10.1186/s12977-014-0122-8
|View full text |Cite
|
Sign up to set email alerts
|

Cross-clade simultaneous HIV drug resistance genotyping for reverse transcriptase, protease, and integrase inhibitor mutations by Illumina MiSeq

Abstract: BackgroundViral resistance to antiretroviral therapy threatens our best methods to control and prevent HIV infection. Current drug resistance genotyping methods are costly, optimized for subtype B virus, and primarily detect resistance mutations to protease and reverse transcriptase inhibitors. With the increasing use of integrase inhibitors in first-line therapies, monitoring for integrase inhibitor drug resistance mutations is a priority. We designed a universal primer pair to PCR amplify all major group M H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 42 publications
2
27
0
Order By: Relevance
“…Overall, our results suggested that minor resistant variants may emerge de novo shortly after transmission, when the small effective population size limits efficient purge by natural selection (30,31). Future studies using recent sequencing technologies that provide longer reads and are less prone to single-base errors (MiSeq or PacBio with or without Primer ID) (32,33) or single-genome amplification/ Sanger sequencing in different settings (i.e., ART-experienced HIV-infected source partners) within a similar Bayesian framework would be informative for detecting clinically relevant minority variants and investigating their propensity for transmission.…”
Section: Discussionmentioning
confidence: 78%
“…Overall, our results suggested that minor resistant variants may emerge de novo shortly after transmission, when the small effective population size limits efficient purge by natural selection (30,31). Future studies using recent sequencing technologies that provide longer reads and are less prone to single-base errors (MiSeq or PacBio with or without Primer ID) (32,33) or single-genome amplification/ Sanger sequencing in different settings (i.e., ART-experienced HIV-infected source partners) within a similar Bayesian framework would be informative for detecting clinically relevant minority variants and investigating their propensity for transmission.…”
Section: Discussionmentioning
confidence: 78%
“…Deep sequencing. The three different types of deep sequencing instruments currently in use include Illumina MiSeq (296,297), the Roche 454/GS Junior pyrosequencer (295,298,299), and the Ion PGM 200 sequencer (300). The operational principles of these methods are similar and can be completed to yield DRM reports in 1 to 2 days.…”
Section: Genotyping Methodsologiesmentioning
confidence: 99%
“…For the required template enrichment, the current fullgenome protocols rely on amplification of large genomic regions with subtype-wide primers and therefore perform less well at viral loads below 1000-3000 copies/ml, making these assays currently more appropriate for surveillance efforts than for monitoring of individual patients [28,29]. However, several studies have already shown that experienced laboratories can achieve accurate NGS results at frequencies as low as 1% [30,31 ,32,33 ].…”
Section: Ultra-wide Ngs For Genotypic Drug Resistance Testingmentioning
confidence: 99%